Investment Revolution in Heating: The Rubtsovsk Model. - Kosogova, E.A. (Problems of Economic Transition, 2022)
The text is based on the presentation of E.A. Kosogova during the round table "Reforming the Russian Heat and Power Industry: Results, Current Problems and Challenges," which was held on May 30, 2019 at the Institute of Economics and Organization of Industrial Production of the Siberian Branch of the Russian Academy of Sciences. In 2016–2017, the Siberian Generating Company LLC comprehensively reconstructed the heat supply system of the city of Rubtsovsk (Altai Krai), including the modernization of the main heat networks and the generating equipment of the South Thermal Power Plant. E.A. Kosogova spoke about the specific organization and financing of the project, as well as its problems and solutions.